Improvement of Health Independence through “Dogima” Program - Nurhasanah, Nurhasanah; Alameka, Faza; Ardan, M; Caroline, Audy Nabila; Andrea, Reza (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
The partner's issues were related to environmental health and digital marketing literacy. This area often experienced floods, lacked organized waste management, and had low awareness and knowledge of domestic waste management. Besides that, the partner had an interest in cultivating ornamental plants with economic value. “Dogima” program was a collaboration between health and digital marketing education. Health education includes training on domestic waste management, especially the separation of organic and inorganic waste, which is then used as raw material for composting. Digital marketing education involves training in creating digital posters as marketing for selling plants. The aim of this activity was to enhance the partner's skills in transforming domestic waste into economical products. The stages of the activity start with planning, socialization, training, mentoring, and evaluation. The implementation of “Dogima” program found that there was an 89% increase in knowledge and a 92% improvement in skills in domestic waste management and created a simple poster for digital marketing on social media. This knowledge and skill improvement could improve the quality of environmental health and digital marketing capabilities which will increase the health independence of partners. The partner's response to this activity was very positive and allowed for its continuous implementation.